EFFECT OF SILANIZED TITANIUM DIOXIDE ON TENSILE STRENGTH OF SELF-CURED ACRYLIC RESIN - Helmi Fathurrahman; Teguh Tri Widodo; Wirda Yunita Darwis (Jurnal Medali, 2022)
Background: Self-curing acrylic resin is a material used to make artificial tooth bases as well as reparate it when there is a fracture on the tooth bases. Titanium dioxide is one of the metal oxides that can be added to acrylic resins as an addition materials. This study aims to determine the effect of adding silanized titanium dioxide filler (TiO2) on tensile strength of self-cured acrylic resin. Methods: This study is a true experimental laboratory study with the design post test only group design, using self-cured acrylic resin plates amounting to 24 plates measuring 165mm x 13mm x 3mm divided into groups of 4 with adding and without adding silanized TiO2. The self-cured acrylic resin plate mixed with silanized TiO2 was tested for tensile strength with a Universal Testing Machine. The data obtained were analyzed with Kruskal-Wallis test. Results: There is an effect of adding titanium dioxide filler (TiO2) to the tensile strengthof self-cured acrylic resin with the highest tensile strength value at 26,1327 MPa ± 2,29608.Conclusion: 5% titanium dioxide filler showed the highest tensile strength than other groups.